Implementation Science is Imperative to the Optimization of Obstetric Care - Hamm, Rebecca F.; Iriye, Brian K.; Srinivas, Sindhu K. (American Journal of Perinatology, 2020)
In an effort aimed at improving outcomes, obstetric teams have enacted comprehensive care bundles and other clinical tools. Yet, these practices have had limited degrees of success on a national scale. Implementation science aims to bridge the divide between the development of evidence-based interventions and their real-world utilization. This emerging field takes into account key stakeholders at the clinician, institution, and health policy levels. Implementation science evaluates how well an intervention is or can be delivered, to whom, in which context, and how it may be up-scaled and sustained. Other medical disciplines have embraced these concepts with success. The frameworks and theories of implementation science can and should be incorporated into both obstetric research and practice. By doing so, we can increase widespread and timely adoption of evidence and further our common goal of decreasing maternal morbidity and mortality.Key Points
Keywords: obstetrics; implementation science; evidence-based practices; maternal morbidity